2022
DOI: 10.3390/ijms232314684
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of Transcription Factors Involved in Geraniol Biosynthesis in Rosa chinensis

Abstract: Fragrance is an important characteristic of rose flowers and is largely determined by the terpenes. Rose has a unique NUDX1 (NUDIX HYDROLASES 1)–dependent monoterpene geraniol biosynthesis pathway, but little is known about its transcriptional regulation. In this study, we characterized two China rose (Rosa chinensis) materials from the ‘Old Blush’ variety with contrasting aromas. We profiled the volatile metabolome of both materials, and the results revealed that geraniol was the main component that distingui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 54 publications
(61 reference statements)
0
3
0
Order By: Relevance
“…Since the discovery of the first linalool synthase gene in fairy fans ( Clarkia breweri ) [ 23 ], many TPS genes have been cloned and investigated in Arabidopsis ( Arabidopsis thaliana ) [ 24 ], citrus ( Citrus sinensis ) [ 25 ], grape ( Vitis vinifera ) [ 26 ], tomato ( Solanum lycopersicum ) [ 27 ], etc. Terpene biosynthesis is regulated though not only by key TPSs but also by the activity of transcription factors (TFs) [ 28 ]. Many TFs involved in terpene biosynthesis have been identified, such as AP2/ERF (APETALA2/ethylene-responsive factor), MYB, WRKY, bHLH (helix-loop-helix), bZIP (basic leucine zipper), and NAC (NAM, ATAF and CUC) families [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Since the discovery of the first linalool synthase gene in fairy fans ( Clarkia breweri ) [ 23 ], many TPS genes have been cloned and investigated in Arabidopsis ( Arabidopsis thaliana ) [ 24 ], citrus ( Citrus sinensis ) [ 25 ], grape ( Vitis vinifera ) [ 26 ], tomato ( Solanum lycopersicum ) [ 27 ], etc. Terpene biosynthesis is regulated though not only by key TPSs but also by the activity of transcription factors (TFs) [ 28 ]. Many TFs involved in terpene biosynthesis have been identified, such as AP2/ERF (APETALA2/ethylene-responsive factor), MYB, WRKY, bHLH (helix-loop-helix), bZIP (basic leucine zipper), and NAC (NAM, ATAF and CUC) families [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, JsTPS3, a terpenoid-related gene, has been found to enhance the β-ocimene production in jasmine [7]. In addition, transcription factors (TFs) such as MYB, bHLH, and WRKY families are also involved in the biosynthesis of terpenoids [10,11]. Recently, Qi et al, 2022 reported that many MYB-, bHLH-, and WRKY-binding elements were significantly enriched in promoter regions of TPS genes in single-petal J. sambac (cultivar, 'Danbanmoli') [11].…”
Section: Introductionmentioning
confidence: 99%
“…The WRKY TFs play important roles in regulating plant development, response to stresses, and secondary metabolite biosynthesis [12,17,18]. In this respect, many WRKY genes have been found to be involved in the regulation of terpenoid genes in several aromatic plant species [8,10]. For example, some monoterpenes in Osmanthus fragrans are regulated by OfWRKY TFs [16].…”
Section: Introductionmentioning
confidence: 99%